Pengaruh Disiplin Terhadap Produktivitas Kerja Karyawan PDAM Tirta Sakti Kabupaten Kerinci - Emilya Gusmita (Ebisma (Economics, Business, Management, & Accounting Journal), 2024)
This research aims to conduct a study on discipline with the work productivity of employees of PDAM Tirta Sakti Sitinjau Laut Branch, in this study amounted to 33 people from PDAM Tirta Sakti Sitinjau Laut Branch employees. The results showed that there was an influence between discipline on the work productivity of employees of PDAM Tirta Sakti Sitinjau Laut Branch, Kerinci Regency with a strong influence category.